Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper studies Luxembourg's economic growth performance of the past two decades with a view to shedding light on the growth prospects and fiscal implications. The paper investigates whether the recent weakness in activity is largely transitory or whether it heralds a new era of lower potential output growth. The paper also explains one option for reforming the pay-as-you-go pension pillar, which is to link pension benefits to the contributions base through a 'solidarity factor.'.